2003
DOI: 10.1257/000282803322157115
|View full text |Cite
|
Sign up to set email alerts
|

Relational Incentive Contracts

Abstract: Standard incentive theory models provide a rich framework for studying informational Incentive problems arise in many economic relationships. Contracts that tie compensation to performance can mitigate incentive problems, but writing completely effective contracts is often impractical.1 As a result, real-world incentives frequently are informal. Within firms, compensation and promotion often are based on difficult to verify aspects of performance such as teamwork, leadership, or initiative. Employees underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
823
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 917 publications
(869 citation statements)
references
References 31 publications
20
823
1
4
Order By: Relevance
“…In the present context, the bilateral incentive problems comes from the ability of either party to breach the contract. In the relational contracting literature which is closer to our framework, pooling incentives on both sides of the relationship is also a common feature as it was shown by Levin (2003) in a different informational context.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In the present context, the bilateral incentive problems comes from the ability of either party to breach the contract. In the relational contracting literature which is closer to our framework, pooling incentives on both sides of the relationship is also a common feature as it was shown by Levin (2003) in a different informational context.…”
Section: Introductionmentioning
confidence: 62%
“…18 Second, stationarity may be required if the buyer starts trading with several potential sellers at different points in time and no third-price discrimination across sellers is possible. Finally, Levin (2003) has also shown that stationary contracts remain optimal when types are independently drawn over time even under limited enforcement. Our analysis below unveils to what extent stationarity should be taken with a word of caution when types are persistent.…”
Section: Costly Enforcement: Setting Up the Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The higher the discount factor, the higher is the present value of the ongoing relationship relative to the present value of reneging on the contract. When this 'punishment'from reneging increases, the parties are able implement higher-powered incentives without running the risk of opportunism (see Levin, 2003).…”
Section: Trust and Optimal Incentivesmentioning
confidence: 99%
“…Moreover, the large majority of 2 Schmidt and Schnitzer (1995) and Baker, Gibbons and Murphy (1994) analyze models with both veri…able and non-veri…able variables, but the veri…ability of a given action or signal is exogenously given. Other models that address the relationship between veri…able and non-veri…able variables are Bernheim and Whinston (1998) Levin (2003) who makes a de…nite treatment of relational contracts with asymmetric information. But neither of these papers open for costly contracting and probabilistic enforcement, like we do.…”
Section: Introductionmentioning
confidence: 99%